Karakteristik Akhlak Islam dan Metode Pembinaan Akhlak dalam Pemikiran Al-Ghazali - Ira Suryani; Hasan Ma’tsum; Sri Suharti; Dewi Lestari; Akublan Siregar (Islam & Contemporary Issues, 2021)
One of the main missions of Islam is to perfect human morals. With this mission, humans are expected to become moral beings, namely creatures who are fully responsible for all their actions. Akhlak al Karimah which is taught in Islam is the ultimate goal that must be adhered to by every Muslim. Someone who wants to get true happiness, should make morals as a basis for acting and behaving. On the other hand, people who do not care about moral development are people who have no purpose in life.